Health technology assessment of surgical robots: a mini-review of a rapidly evolving field - Zhang, Tiantian; Zhong, Yunwu; Zeng, Jia; Liu, Gordon G. (Frontiers in Public Health, 2025)
BackgroundSurgical robots enhance precision and enable minimally invasive procedures but pose challenges for traditional Health Technology Assessment (HTA) due to high costs, organizational disruption, and rapid iteration.Core contentThis review first reviews the development trajectory of surgical robots and their applications in modern surgery. It then elaborates on the fundamental definition and value dimensions of HTA, highlighting the IDEAL framework specifically designed for evaluating complex surgical innovations and its tailored recommendations for surgical robots. Then provides a detailed analysis of specific challenges encountered in HTA of surgical robots.DiscussionThis review thoroughly examines two core controversies in current assessment paradigms: the debate over the roles of randomized controlled trials (RCTs) vs. real-world evidence (RWE) in the evidence hierarchy, and the paradigm tension between traditional cost-effectiveness analysis and the broader Value-Based Healthcare (VBHC) approach. Key identified research gaps include: the lack of standardized HTA frameworks accounting for medical device characteristics, insufficient long-term patient-centered outcomes and system-level impact data. Looking ahead, the assessment of surgical robots is evolving toward dynamic, iterative “living” HTA models, urgently requiring new paradigms to evaluate AI-integrated intelligent systems and ultimately striving toward a comprehensive assessment system integrating broad value dimensions with a global perspective.ConclusionStatic HTA methods, primarily designed for pharmaceuticals, are inadequate for complex, rapidly evolving platforms like surgical robots. Establishing a more dynamic, holistic, and standardized assessment paradigm is crucial to ensure safe, effective, and cost-efficient benefit for patients and society.